Efektivitas Blended Learning Berbasis LMS dengan Model Pembelajaran Inkuiri pada Materi Fluida Statis terhadap Penguasaan Konsep Siswa - Noor Laily Akhmalia; Wayan Suana; Nengah Maharta (JIPFRI (Jurnal Inovasi Pendidikan Fisika dan Riset Ilmiah), 2018)
This research was aimed to find out the effectiveness of blended learning on LMS with inquiry learning mode to students concept mastery. The research sample used was 68 students of Senior High School in Bandarlampung. In experimental class, the researcher used blended learning based on LMS with inquiry learning mode, while in control class the researcher used conventional mode. The research design used was Pretest-Posttest Control Group Design. After all data were collected, the data were tested for normallity, homogeneity, and ancova. Based on the result of ANCOVA with Fcount > Ftable (15,45 > 3,98), it shows that there is the difference in the average of students concept mastery in experimental class and control class which means that blended learning based on LMS with inquiry learning mode gives a significant impact to the student concept mastery. In addition, it can effectively enhance the student concept mastery proven by the difference of N-Gain average in experimental class which is 0,84 with the high category and in control class 0,70 with the average category.